Kesejahteraan Dalam Model Bisnis Startup : Studi Evaluatif Pada Aplikasi Pawtners - Ariahmand Saragih; Chintia Ni; Claudio Cassano Nistelrooy Purba; Haga Creis Tentry; Ika Fitriani Sukur; Matthew Alessandro Sianipar; Yeftika Mutiara Sianturi (Journal on Education, 2024)
This study aims to evaluate the feasibility of Pawtners, an online pet adoption platform focused on animal welfare. The research reviews user reception of the application, emphasizing the importance of user interface (UI) and user experience (UX) design in promoting pet adoption. Data were collected through a survey involving 46 respondents, most of whom were students. The results show that the majority of respondents prefer adopting pets over purchasing, with cats and dogs being the most favored. Respondents also rated Pawtners' UI/UX as attractive and user-friendly. These findings suggest that the application has great potential in supporting a more structured and responsible pet adoption process.